Social Internet Use by People With Intellectual Disabilities: A Systematic Review and Thematic Synthesis of Qualitative Studies. - van Alem, Johanna L. L.; Frielink, Noud; Embregts, Petri J. C. M. (Journal of Intellectual Disability Research, 2025)
Introduction: Although existing research has explored both the benefits and risks associated with social internet use amongst people with intellectual disabilities (ID), a comprehensive understanding of the underlying reasons for this engagement is still lacking. This systematic review synthesizes literature investigating the reasons for social internet use amongst people with ID. Methods: Eight electronic databases (Cinahl, Cochrane, Embase, ERIC, Google Scholar, Medline, PsycINFO and Web of Science) were systematically searched in June 2023 and November 2024 and screened using active machine learning techniques. Studies were considered for inclusion if they qualitatively described the reasons, motivations and personal opinions of people with ID regarding their social internet use in English and were published in peer‐reviewed journals. Caregivers' insights were included if individuals could not verbally communicate directly. Only voluntary social internet use was considered; interventions were excluded unless preintervention views on social internet use were reported. Risk of bias was assessed using the Mixed Methods Appraisal Tool (MMAT; Hong et al. 2018). Data were extracted using the SPIDER tool and analysed using thematic synthesis. Results: In total, 21 relevant articles were identified. Most studies described social internet use in Western contexts (n = 19), primarily amongst adults (n = 16). Four articles specifically addressed social internet use during COVID‐19. Only seven studies explicitly reported participants' level of ID, with six focusing on mild‐to‐moderate ID and one on profound and multiple ID. Four themes emerged: a feeling of fitting in (n = 12), maintaining connections (n = 16), making new connections (n = 14) and enhancing autonomy and empowerment (n = 10). Discussion: The findings underscore the importance of social internet use in fostering feelings of inclusion, connectedness and autonomy amongst people with ID. These insights can guide researchers and caregivers in developing tailored support strategies that both maximize the benefits and mitigate the risks of online social engagement for this population. By understanding the specific reasons behind social internet use, caregivers can offer more personalized guidance that aligns with the individual needs and preferences of people with ID. The review also highlights a need for future research to adhere to reporting guidelines to enhance transparency and quality in the field.